Strategi Pemulihan Pariwisata Kota Seribu Klenteng, Kota Singkawang di Masa Pandemi COVID-19: Strategi Pemulihan Pariwisata Kota Seribu Klenteng, Kota Singkawang di Masa Pandemi COVID-19 - Stephanie Rosanto; Sofiani Sofiani (Jurnal Manajemen Perhotelan dan Pariwisata, 2022)
Various tourist attractions in Indonesia were closed due to the impact of the COVID-19 pandemic and caused a drastic reduction in tourists visiting Indonesia. Tourism supporting sectors. Singkawang City is one of 14 regencies or cities in West Kalimantan Province which is 145 km north of Pontianak City. Judging from the type of data, this study uses a mixed-method approach, namely research that combines two approaches, namely quantitative and qualitative. The strategy carried out by the mayor of Singkawang in the development of regional tourism, which includes the provision of tourism facilities and infrastructure, regional tourist attractions, increasing community participation and increasing the participation of the private sector. Local governments must make various efforts in the development of facilities and infrastructure. The focus on developing tourist attractions in Singkawang is done by developing tourist objects in the area, natural tourism in the Singkawang area. gold then now this lake is improving by increasing the accessibility provided by the government making this lake attractive. The participation of the private sector in the Singkawang city area is very good where this year the government, namely the mayor of Singkawang, has received assistance for the development of the area around the Serantangan lake by investors. Community Participation In developing regional tourism objects in Nganjuk Regency, it is very important that the active role of the surrounding community is needed.